Habitus Tensions between NU's Santri and Students: Religious Education Cultural Transformation in the Disruption Era - Muhammad Azlan Lubis; Annuha , Ahmad Nabil (LAKPESDAM MWCNU Palengaan, 2025)
Technological disruption has created a new arena for the distribution of religious knowledge and authority, bringing together two distinct habitus: the pesantren-based traditional habitus of santri and the academic habitus of NU university students shaped by higher education. This study aims to explore the symbolic and epistemological conflicts between the two groups, as well as the reproduction and contestation of cultural and symbolic capital in the digital context. Using a qualitative approach and Pierre Bourdieu’s theoretical framework, data were collected through social media observation and semi-structured interviews. The findings reveal that NU students utilize digital media to renegotiate religious identity, while pesantren institutions retain traditional authority structures. This tension reflects a hysteresis effect and a shift in symbolic authority within the NU community. Disrupsi teknologi menciptakan arena baru distribusi pengetahuan dan otoritas keagamaan, mempertemukan dua habitus berbeda: habitus santri berbasis pesantren dan habitus akademik mahasiswa NU yang dibentuk oleh perguruan tinggi. Penelitian ini bertujuan memahami konflik simbolik dan epistemologi antar keduanya, serta reproduksi dan kontestasi modal kultural-simbolik dalam konteks digital. Menggunakan pendekatan kualitatif dan teori Pierre Bourdieu, data dikumpulkan melalui observasi media sosial dan wawancara semi-struktural. Hasil menunjukkan bahwa mahasiswa NU memanfaatkan media digital untuk menegosiasikan identitas keagamaan, sedangkan pesantren bertahan pada otoritas tradisional. Ketegangan ini menunjukkan hysteresis effect dan pergeseran otoritas simbolik dalam komunitas NU.